A preliminary study on functional activation and connectivity during frustration in youths with bipolar disorder. (20th September 2020) - Ross, Andrew J.; Roule, Alexandra L.; Deveney, Christen M.; Towbin, Kenneth E.; Brotman, Melissa A.; Leibenluft, Ellen; Tseng, Wan‐Ling
Abstract: Objectives: Frustration is associated with impaired attention, heightened arousal, and greater unhappiness in youths with bipolar disorder (BD) vs healthy volunteers (HV). Little is known about functional activation and connectivity in the brain of BD youths in response to frustration. This exploratory study compared BD youths and HV on attentional abilities, self‐reported affect, and functional activation and connectivity during a frustrating attention task. Methods: Twenty BD (Mage  = 15.86) and 20 HV (Mage  = 15.55) youths completed an fMRI paradigm that differentiated neural responses during processing of frustrating feedback from neural responses during attention orienting following frustrating feedback. We examined group differences in (a) functional connectivity using amygdala, inferior frontal gyrus (IFG), and striatum as seeds and (b) whole‐brain and regions of interest (amygdala, IFG, striatum) activation. We explored task performance (accuracy, reaction time), self‐reported frustration and unhappiness, and correlations between these variables and irritability, depressive, and manic symptoms. Results: Bipolar disorder youths, relative to HV, exhibited positive IFG‐ventromedial prefrontal cortex (vmPFC) connectivity yet failed to show negative striatum‐insula connectivity during feedback processing. Irritability symptoms were positively associated with striatum‐insula connectivity during feedback processing. Moreover, BD vs HV youths showed positive IFG‐parahippocampal gyrus (PHG)/periaqueductal gray (PAG) connectivity and negative amygdala‐cerebellum connectivity during attention orienting following frustration. BD was not associated with atypical activation patterns. Conclusions: Positive IFG‐vmPFC connectivity and striatum‐insula decoupling in BD during feedback processing may mediate heightened sensitivity to reward‐relevant stimuli. Elevated IFG‐PAG/PHG connectivity in BD following frustration may suggest greater recruitment of attention network to regulate arousal and maintain goal‐directed behavior.